2010
DOI: 10.2478/v10042-010-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vasoactive intestinal peptide, pituitary adenylate cyclase-activating polypeptide and neuropeptide Y-ergic structures of the enteric nervous system in the carcinoma of the human large intestine.

Abstract: This investigation was aimed at immunohistochemical analysis of potential changes in the enteric nervous system caused by cancer of the large intestine. In this purpose, neurons and nerve fibers of intestinal plexuses containing neuropeptides: vasoactive intestinal peptide (VIP), pituitary adenylate cyclase-activating polypeptide (PACAP) and neuropeptide Y (NPY), in pathologically changed part of the large intestine were microscpically observed and compared. Samples were taken from patients operated due to can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 39 publications
(52 reference statements)
3
25
0
Order By: Relevance
“…As a result they confirm previous studies, where expression of PACAP has been described in the GI tract of various species, including humans (8,10,14,19,20), and suggest that also in dog this peptide plays, known in other species, important multiple biological functions for optimal functioning of the gastrointestinal tract. Its role has been shown in processes, such as the gut motility, regulation of neurotransmitter release, as well as secretion of the gastric and intestinal glands (6,19,29,30).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As a result they confirm previous studies, where expression of PACAP has been described in the GI tract of various species, including humans (8,10,14,19,20), and suggest that also in dog this peptide plays, known in other species, important multiple biological functions for optimal functioning of the gastrointestinal tract. Its role has been shown in processes, such as the gut motility, regulation of neurotransmitter release, as well as secretion of the gastric and intestinal glands (6,19,29,30).…”
Section: Discussionsupporting
confidence: 90%
“…PACAP-like immunoreactivity has been observed in neuronal structures supplying various fragments of the GI tract in numerous species, especially within elements that innervate the circular or longitudinal smooth muscle layers as well as intestinal glands (10,14,19,20,30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is in accordance with immunohistochemical analysis of human sigmoid colon and rectum tumors, where a less dense PACAP immunoreactive nerve fi ber network was observed in the myenteric and submucosal plexi than in normal controls [ 88 ]. Another study found that in patients with symptomatic diverticular disease signifi cantly higher PACAP levels can be detected along with increases in other neuropeptides within the mucosal plexus.…”
Section: Effects Of Pacap In Large Intestinal Infl Ammationsupporting
confidence: 85%
“…Since our previous study revealed that the expression of neuropeptides (16), including GAL (17), in the ENS ganglia was altered when in close proximity to CRC invasion, the present study additionally aimed to determine the GAL levels in the homogenates of CRC tumors and two dissected sections of the colon wall (mucosa with submucosa and the muscularis externa) both proximal to the tumor and distant from the tumor, which served as the control. Since a reduction in myenteric plexus size and decomposition has been observed in the colon wall of CRC patients (18), the GAL-immunoreactive (GAL-Ir) myenteric plexuses in the vicinity of and distant from CRC invasion in the colon wall were quantitatively assessed.…”
Section: Introductionmentioning
confidence: 99%